Managing communal pasture areas for goats in Inhassoro District, Mozambique: A manual for trainers - Boogaard, Birgit K.; Cosijn, M.; Marble, Y.; Hendrickx, Saskia C.J. (International Livestock Research Institute, 2012)
The European Commission-funded project, Small ruminant value chains as platforms for reducing poverty and increasing food security in dryland areas of India and Mozambique (imGoats) aims to increase incomes and food security in a sustainable manner by enhancing pro-poor small ruminant value chains in India and Mozambique. The project is implemented by the International Livestock Research Institute (ILRI) in collaboration with BAIF Development Research Foundation in India and CARE Mozambique. The project uses innovation platforms as a participatory way of identifying and testing interventions aimed at increasing smallholder goat productivity.